Asymptotic dimension and the disk graph II. Issue 3 (12th March 2019) - Hamenstädt, Ursula
Abstract: We show that the asymptotic dimension of a hyperbolic relatively hyperbolic graph is finite, provided that this holds true uniformly for the peripheral subgraphs and for the electrification. We use this to show that the asymptotic dimension of the disk graph of a handlebody of genus g ⩾ 2 is at most quadratic in the genus.